2019
DOI: 10.1002/qua.26134
|View full text |Cite
|
Sign up to set email alerts
|

External Electric Field—Phenyl interaction boosts hydrosilylation of substituted alkynes to α‐vinylsilane

Abstract: The hydrosilylation of terminal alkyne is the most straightforward and atom‐economy method to generate α‐vinylsilane. In the present paper, the acetylene and phenylacetylene hydrosilylation reactions were firstly studied by imposing external electric field (EEF) as a catalyst at the level of ωB97XD/TZVP. The results demonstrated that the oriented negative FY direction is the optimal direction, which mostly reduced the reaction barriers. Further computations indicated that the larger the EEF, the lower the barr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 78 publications
0
1
0
Order By: Relevance
“…Since Shaik et al reported that the EEF controls the selectivity of iron-oxo porphyrin with propene, relevant literature studies gradually sprung up in theory and the experiment . Upon perusal of this work, we were inspired and tried to explore hydrofunctionalization reactions (such as hydroboration, hydrohydrazination, and hydrosilyation) by EEF as an “invisible” catalyst. According to this precedent, we first studied the EEF-mediated allylamine hydrothiolation reaction in this manuscript.…”
Section: Introductionmentioning
confidence: 99%
“…Since Shaik et al reported that the EEF controls the selectivity of iron-oxo porphyrin with propene, relevant literature studies gradually sprung up in theory and the experiment . Upon perusal of this work, we were inspired and tried to explore hydrofunctionalization reactions (such as hydroboration, hydrohydrazination, and hydrosilyation) by EEF as an “invisible” catalyst. According to this precedent, we first studied the EEF-mediated allylamine hydrothiolation reaction in this manuscript.…”
Section: Introductionmentioning
confidence: 99%